The gender of commute - Masa Bratusa (Cidades, Comunidades e Território)
It is inadequate that the phrase “women in architecture” embeds primarily the names of unknown or long forgotten female architects, or refers to contemporary female architects who are labelled and therefore indefinably distinguished from other professionals in their field. Although the numbers and importance of the roles that women are claiming in architecture, hence the production of space, today are growing, the questions which can be associated with the meaning of the phrase “women in architecture” remain and become more complex. The binary nature of the phrase calls for a deeper insight into the position of women in today’s built environment: who are the (female) architects of our world and what role they play can hardly be separated from questions related to the space which women are permitted, by cultural as well as socio-economic circumstances, to participate in or have control over.The deterioration of territorial rights, which progressed in parallel with perceived emancipation of women, may play a crucial role in our understanding of the female architect’s commission and her responsibility to women’s everyday experience.